Metabolomic profiling and 16 S rRNA metabarcoding of endophytes of two Aloe species revealed diverse metabolites - Cynthia Marokane-Radebe; Adekunle Raimi; Stephen Amoo; Rasheed Adeleke (AMB Express)
Abstract Aloe species are often used interchangeably for medicinal and cosmeceutical applications, presenting a challenge to the biological efficacy consistency of some herbal preparations. Sustainable production of high-quality commonly used medicinal plants remains a limitation for commercialisation. Thus, this study investigated the potential for plant substitution by examining bacterial endophytes capable of producing similar host plant secondary metabolites. The metabolite profiles and endophytic bacterial communities of endangered Aloe lettyae were compared with those of Aloe longibracteata using nuclear magnetic resonance spectroscopy and 16 S rRNA gene sequencing. Only 15 metabolites were significantly different between A. lettyae and A. longibracteata based on metabolite concentrations. However, both plants’ functionality and potential application remain comparable. Phytohormones, including indole-3-acetate and 5-hydroxyindole-3-acetate, were more concentrated in A. lettyae than A. longibracteata. Metabolites such as tyrosine, allantoin, and myo-inositol, with human health benefits, were annotated in both species. Aloe lettyae harboured a phylogenetically diverse bacteria community compared to A. longibracteata, with a higher richness of bacterial species, indicating a likelihood of diverse metabolic capabilities among the bacteria. Dominant endophytes, including Bacillus, Comamonas, and Pseudomonas, possess enzymes contributing to various metabolic pathways. The enzymes have the potential to impact the synthesis, or breakdown of plant metabolites, consequently influencing the overall metabolic composition of the host plant. Therefore, this study supports the interchangeability of A. lettyae and A. longibracteata due to their ability to produce similar metabolites, and although the Aloe species exhibit phylogenetically diverse endophytic communities, the feasibility of utilizing their endophytes as producers of secondary metabolites remains viable. Graphical abstract